Hypochloraemia following admission to hospital with heart failure is common and associated with an increased risk of readmission or death: a report from OPERA-HF. Issue 1 (13th December 2021) - Cuthbert, J J; Brown, O I; Urbinati, A; Pan, D; Pellicori, P; Dobbs, K; Bulemfu, J; Kazmi, S; Sokoreli, I; Pauws, S C; Riistama, J M; Cleland, J G F; et al.
Abstract: Aims: Hypochloraemia is common in patients hospitalized with heart failure (HF) and associated with a high risk of adverse outcomes during admission and following discharge. We assessed the significance of changes in serum chloride concentrations in relation to serum sodium and bicarbonate concentrations during admission in a cohort of 1002 consecutive patients admitted with HF and enrolled into an observational study based at a single tertiary centre in the UK. Methods and results: Hypochloraemia (<96 mmol/L), hyponatraemia (<135 mmol/L), and metabolic alkalosis (bicarbonate >32 mmol/L) were defined by local laboratory reference ranges. Outcomes assessed were all-cause mortality, all-cause mortality or all-cause readmission, and all-cause mortality or HF readmission. Cox regression and Kaplan–Meier curves were used to investigate associations with outcome. During a median follow-up of 856 days (interquartile range 272–1416), discharge hypochloraemia, regardless of serum sodium, or bicarbonate levels was associated with greater all-cause mortality [hazard ratio (HR) 1.44, 95% confidence interval (CI) 1.15–1.79; P = 0.001], all-cause mortality or all-cause readmission (HR 1.26, 95% CI 1.04–1.53; P = 0.02), and all-cause mortality or HF readmission (HR 1.41, 95% CI 1.14–1.74; P = 0.002) after multivariable adjustment. Patients with concurrent hypochloraemia and natraemia had lower haemoglobin and haematocrit, suggesting congestion; those with hypochloraemia and normal sodium levels had more metabolic alkalosis, suggesting decongestion. Conclusion: Hypochloraemia is common at discharge after a hospitalization for HF and is associated with worse outcome subsequently. It is an easily measured clinical variables that is associated with morbidity or mortality of any cause. Graphical abstract: